One week triple therapy for Helicobacter pylori: a multicentre comparative study. Issue 6 (1st December 1997) - Misiewicz, J J; Harris, A W; Bardhan, K D; Levi, S; O'Morain, C; Cooper, B T; Kerr, G D; Dixon, M F; Langworthy, H; Piper, D
Abstract : Background— Eradication of Helicobacter pylori cures and prevents the relapse of duodenal ulceration and also results in histological resolution of chronic active gastritis. Aim —To compare four treatment regimens lasting seven days of a proton pump inhibitor and two antibiotics in the eradication of H pylori . Patients —Men or women with H pylori positive duodenal ulceration or gastritis, or both. Methods —A single blind, prospectively randomised, parallel group, comparative, multicentre study. After a positive CLO test, patients underwent histology, H pylori culture, and a 13 C urea breath test to confirm H pylori status. Treatment with one of four regimens: LAC, LAM, LCM, or OAM, where L is 30 mg of lansoprazole twice daily, A is 1 g of amoxycillin twice daily, M is 400 mg of metronidazole twice daily, C is 250 mg of clarithromycin twice daily, and O is 20 mg of omeprazole twice daily, was assigned randomly. A follow up breath test was done at least 28 days after completing treatment. Results — H pylori eradication (intention to treat) was 104/121 (86.0%) with LAC, 87/131 (66.4%) with LAM, 103/118 (87.3%) with LCM, and 94/126 (74.6%) with OAM. There was a significant difference (p < 0.001) in the proportion of patients in whom eradication was successful between LAC and LCM when compared with LAM, but no significant difference (p = 0.15) between LAM and OAM. Metronidazole resistance before treatment was identified as a significant prognostic factor with regard to eradication of H pylori . The regimens which contained metronidazole were significantly less effective than those without metronidazole in the presence of pretreatment resistant H pylori . There was no difference among the treatment groups with regard to the incidence and severity of adverse events reported. Conclusions —All four treatment regimens were safe and effective in eradicating H pylori in the patient population studied. LAC was the most efficacious treatment in patients with pretreatment metronidazole resistant H pylori, and was significantly better than LAM and OAM in this group of patients.